A Series of Photosensitizes for Fe3+ in Aqueous Solution and Cells With Colorimetric and Fluorescent Channels: Synthesis and Performance - Xu, Ming; Liao, Jiang-Tao; Chen, Gang; Chen, Yin-Yun; Liu, Dan; Wang, Li-Le (Frontiers in Chemistry, 2022)
Ferrum (Fe) is a widely existed metal element and nearly the most important trace element in living species, including human beings. The design of chemosensors for Fe ions always faces an issue that the d-d transition of Fe(II) and Fe(III) ions makes them efficient electron trappers and energy quenchers. Nearly all fluorescent dyes can not afford such d-d quenching, showing emission turn off effect towards both Fe(II) and Fe(III) ions with poor selectivity. As a consequence, the development for Fe with emission turn on effect and good selectivity shall be continued and updated. In this work, three rhodamine-derived chemosensors modified by different lengths of alkyl chains having electron-donating N and O atoms were synthesized and explored for the selective optical sensing of Fe(III). These chemosensors showed colorimetric and fluorescent emission turn on sensing for Fe(III), showing two sensing channels. These chemosensors showed good selectivity as well, which was assigned to the sieving effect of alkyl chains having electron-donating N and O atoms. It was found that N atom was more effective in associating with Fe(III), compared to O atom. Their fluorescent cell imaging experiment was carried out to confirm their possibility of being used for cell imaging.